Sub-micron scale distributions of trace elements in zircon - Hofmann, A.; Valley, J.; Watson, E.; Cavosie, Aaron; Eiler, J. (Springer, 2009)
Sub-micron scale zoning of Ti concentrations and correlations between concentrations of Ti and other trace elements (P, Ce, and Y) and cathodoluminescent (CL) banding is observed in natural zircons. Ion images were made using the Caltech Microanalysis Center's CAMECA NanoSIMS 50L with an O- primary beam focused to ~300 nm on the sample surface. The high spatial resolution of this technique allows for interrogation of chemical variations at or below the scale of CL banding in natural zircons. Images produced in this manner display two types of correlations among Ti, P, Ce, and Y (which appears to be a proxy for CL intensity): strong (correlation coefficients >0.8) and subtle (correlation coefficients ~0.15-0.4). Strongly correlated images, which display Ti variations of ca. a factor of 3 between adjacent CL bands and overall elevated trace element concentrations in CL-dark bands, were found within an oscillatory-zoned, trace element enriched sector of a CL sector-zoned zircon. Three possible causes for such correlations include: temperature-dependent equilibrium partitioning, trace element partitioning limited by diffusion in the host melt and surface-controlled, non-equilibrium growth. Comparison of our data with the expected results of these processes suggests that: (1) Ti partitioning in zircon is dependent upon non-equilibrium effects in addition to temperature and/or (2) the incorporation of elements that co-vary with Ti in zircon (e.g., Y, P and Ce) is also temperature-dependent. Sub-micron scale, high-Ti regions are also found within Proterozoic Adirondack and >4 Ga Jack Hills zircons as well as trace element enrichments (including Ti) along cracks within Jack Hills zircons. © Springer-Verlag 2009.